Land Use/Land Cover and Natural Hazards: Interactions, Changes, and Impacts - Vojtek, Matej; Petroselli, Andrea; Pelorosso, Raffaele (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on land use/land cover (LULC), natural hazards and their interactions, changes, and impacts. Over the past few decades, the risks due to natural hazards have increased significantly, to a large extent due to changes in LULC, which are triggered mainly by anthropic pressure on landscapes, i.e., urbanization, forest management practices, agricultural practices, and the like. As a result, LULC changes contribute significantly to changes in the variability or magnitude of natural hazards, such as floods, landslides, and erosion. Therefore, this reprint provides a collection of studies focused on the interactions between LULC and different types of natural hazards, which were studied in several research areas around the world.